TRAINING IN CREATING BUSINESS IDENTIFICATION NUMBER TO INCREASE THE CAPACITY OF MSMEs IN GADOBANGKONG: PELATIHAN PEMBUATAN NOMOR INDUK BERUSAHA UNTUK MENINGKATKAN KAPASITAS UMKM DESA GADOBANGKONG - Redjeki, Finny; Himawan, Irfan Sophan; Mulyeni, Sri; Herlina, Herlina (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Technological advancements and recent changes in government policy are not yet fully understood by the public. These developments, which are intended to streamline processes across various sectors-including business sustainability-should be accessible and beneficial to all MSME actors. Objective: This community service activity aimed to raise awareness about the importance of business legality and to assist MSMEs in obtaining a Business Identification Number. Method: The activity was conducted over two days in Gadobangkong Village, involving 30 MSME participants. The service team delivered material on government policies related to online-based business legality, followed by hands-on sessions for creating user accounts and registering businesses to obtain NIBs. Results: Participants successfully created user accounts in the Risk-Based Approach Online Single Submission (RBA OSS) system by registering their National Identity Number and WhatsApp number. Those who completed this step proceeded to register their businesses and obtain NIBs. However, two MSME participants were unable to create OSS accounts due to their NIKs not being recognized by the system. This issue was traced to their ID cards not yet being activated as electronic IDs (e-KTP) in the national civil registration system. Conclusion: All training participants engaged actively in the sessions and were able to follow each step of the business registration process-from account creation to successful issuance of the Business Identification Number.